Asian longhorned beetle complicates the relationship between taxonomic diversity and pest vulnerability in street tree assemblages. Issue 1 (2nd January 2016) - Berland, Adam; Hopton, Matthew E.
Abstract : Urban foresters routinely emphasise the importance of taxonomic diversity to reduce the vulnerability of tree assemblages to invasive pests, but it is unclear to what extent diversity reduces vulnerability to polyphagous (i.e. generalist) pests. Drawing on field data from seven communities in metropolitan Cincinnati, Ohio, USA, we tested the hypothesis that communities with higher diversity would exhibit lower vulnerability to the polyphagous Asian longhorned beetle, which currently threatens the region. Based on street tree compositions and the beetle's host preferences, Asian longhorned beetle threatened up to 35.6% of individual street trees and 47.5% of the total basal area across the study area, but we did not see clear connections between taxonomic diversity and beetle vulnerability among study communities. For example, the city of Fairfield was among the least diverse communities but had the lowest proportion of trees vulnerable to Asian longhorned beetle, whereas the city of Wyoming exhibited high diversity and high vulnerability. On the other hand, Forest Park aligned with our original hypothesis, as it was characterised by low diversity and high vulnerability. Our results demonstrate that relatively high taxonomic diversity in street tree assemblages does not necessarily lead to reduced vulnerability to a polyphagous pest. Considering the threats posed by polyphagous pests, selecting a set of relatively pest resistant trees known to perform well in urban areas may promote long-term stability better than following simple heuristics for maximising taxonomic diversity, but further study is warranted.